Spiro heterocycles bearing piperidine moiety as potential scaffold for antileishmanial activity: synthesis, biological evaluation, and in silico studies - Mounir A. A. Mohamed; Asmaa M. Kadry; Salma A. Bekhit; Mohammed A. S. Abourehab; Kikuko Amagase; Tamer M. Ibrahim; Ahmed M. M. El-Saghier; Adnan A. Bekhit (Taylor & Francis Group, 2023)
New spiro-piperidine derivatives were synthesised via the eco-friendly ionic liquids in a one-pot fashion. The in vitro antileishmanial activity against Leishmania major promastigote and amastigote forms highlighted promising antileishmanial activity for most of the derivatives, with superior activity compared to miltefosine. The most active compounds 8a and 9a exhibited sub-micromolar range of activity, with IC50 values of 0.89 µM and 0.50 µM, respectively, compared to 8.08 µM of miltefosine. Furthermore, the antileishmanial activity reversal of these compounds via folic and folinic acids displayed comparable results to the positive control trimethoprim. This emphasises that their antileishmanial activity is through the antifolate mechanism via targeting DHFR and PTR1. The most active compounds showed superior selectivity and safety profile compared to miltefosine against VERO cells. Moreover, the docking experiments of 8a and 9a against Lm-PTR1 rationalised the observed in vitro activities. Molecular dynamics simulations confirmed a stable and high potential binding to Lm-PTR1.